Contribution of Muslim Women Scholars to Ḥadīth Transmission and Authentication - Mehfooz, Musferah (Islamic Studies, 2021)
Muslim history witnessed many women who mastered the science of ḥadīth and demonstrated their expertise in the science of al-jarḥ wa ’l-ta‘dīl (invalidation and validation of ḥadīth narrators). The science of al-jarḥ wa ’l-ta‘dīl is one of the subtlest and the most important branches of the science of ḥadīth, which assesses the authenticity of the narrations attributed to the Prophet (peace be on him), based on the trustworthiness or otherwise of ḥadīth narrators. Since the beginning of Islamic history, Muslim women constantly took part in narrating, preserving, and memorizing ḥadīths. These efforts continued in the later periods. This study aims to investigate the contribution of these women scholars of ḥadīth (muḥaddithāt), especially of ‘Ā’ishah, the wife of the Prophet, to the transmission and authentication of ḥadīths. Furthermore, it highlights the intellectual contribution of women scholars of ḥadīth in order to encourage contemporary Muslim women to continue the legacy of their predecessors by mastering this science.